2019
DOI: 10.1002/hyp.13412
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the interaction of climate, forest ecosystem, and hydrology to estimate catchment dissolved organic carbon export

Abstract: The potential for increased loads of dissolved organic carbon (DOC) in streams and rivers is a concern for regulating the water quality in water supply watersheds. With increasing hydroclimatic variability related to global warming and shifts in forest ecosystem community and structure, understanding and predicting the magnitude and variability of watershed supply and transport of DOC over multiple time scales have become important research and management goals. In this study, we use a distributed process‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…This lends support to future analyses that consider sensitivity analysis of alternative model structures and parameters to discover dominant processes, as in Mai et al (2020) and Koo et al (2020a). The selected parameters across water quantity and quality-focused metrics would likely be different if TN concentrations were estimated from a process-based model, as in the dynamic mode of RHESSys, instead of statistically as a function of streamflow using WRTDS (e.g., RHESSys and WRTDS estimations are compared in Son et al (2019)).…”
Section: Determining Opportunities For Parameter Reductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This lends support to future analyses that consider sensitivity analysis of alternative model structures and parameters to discover dominant processes, as in Mai et al (2020) and Koo et al (2020a). The selected parameters across water quantity and quality-focused metrics would likely be different if TN concentrations were estimated from a process-based model, as in the dynamic mode of RHESSys, instead of statistically as a function of streamflow using WRTDS (e.g., RHESSys and WRTDS estimations are compared in Son et al (2019)).…”
Section: Determining Opportunities For Parameter Reductionmentioning
confidence: 78%
“…Even though the results are conditional on the specific parameter ranges (Shin et al, 2013), climatic input data and model outputs (Shields and Tague, 2012), and structural equations selected (Son et al, 2019), the resulting parameter identification should be generally useful to inform future studies that use RHESSys or other ecohydrologic models.…”
Section: Hydrologic Model Description: Rhessysmentioning
confidence: 99%
“…(4) RHESSys model (Son et al, 2019) The Regional Hydro-Ecological Simulation System (RHESSys) is a biophysically based, spatially explicit model that has the capacity to simulate both climate and vegetation change impacts and feedbacks between hydrologic processes and ecosystem C and nutrient cycling.…”
Section: Mechanistic Model Methodsmentioning
confidence: 99%
“…RHESSys mainly simulates water pollutants of dissolved nitrogen, dissolved organic carbon, ammonia nitrogen, and nitrate-nitrogen (Figure 8). RHESSys has been applied to simulate the dissolved organic nitrogen distribution [47] and the soluble organic carbon distribution [48] to support local regulation of water quality. Previous studies also suggested that the model performance can be improved by coupling with groundwater and phenology sub-models.…”
Section: Water Qualitymentioning
confidence: 99%